For this case we have that the sum of the angles DEF and FEG is equal to 180 degrees.
Therefore, we have:
![DEF + FEG = 180]()
From here, we clear the FEG angle.
We have then:
FEG = 180 - DEF
Substituting values we have:
FEG = 180 - 129
FEG = 51
Then, on the other hand we have that the sum of the angles FEG and HEG is equal to 180 degrees.
Therefore, we have:
HEG + FEG = 180
From here, we clear the HEG angle:
HEG = 180 - FEG
Substituting values we have:
HEG = 180 - 51
HEG = 129
Answer:
The values of HEG and FEG are:
FEG = 51
HEG = 129